Praktik Peralihan Akad Gadai Ke Jual Beli Dalam Tinjauan Fiqh Muamalah (Studi Kasus Di Desa Gunung Rejo Kecamatan Way Ratai Kabupaten Pesawaran) - Karini, Eti; Mulyadin, Arif; Istiani, Yuni (ASAS, 2022)
The purpose of the study was to find out the Practice of Transferring Pawn Contracts for Sale and Purchase in Gunung Rejo Village, Way Ratai District, Pesawaran Regency. In addition, the study examines the review of Fiqh Muamalah on such Implementation. The type of research used is field research with a qualitative approach. Data collection was conducted through documentation and interviews with pawnshop (rahin) and pawn taker (murtahin). The results of this study indicate that the rahin cannot repay the debt he borrowed, then rahin offers collateral to murtahin with the aim of selling it. But in this case, the selling price is determined by the murtahin which causes the sale and purchase price of the land to be much lower than the actual price in the village. The transition from a pawning contract to buying and selling is not in accordance with the rules of Islamic law, because it does not meet the requirements stipulated in the Fatwa of the National Sharia Council No.25/DSN-MUI/III/2002 or Fiqh Muamalah. If the pawnshop (rahin) cannot repay the loan, the collateral is sold through auction or offered to a third party.Keywords: Fiqh Muamalah, Pawn, Sale and Purchase